Comprehensive analysis of acidic pharyngeal reflux before and after proton pump inhibitor treatment in patients with suspected laryngopharyngeal reflux. Issue 2 (February 2020) - Duricek, Martin; Banovcin, Peter; Halickova, Tatiana; Hyrdel, Rudolf; Kollarik, Marian
Abstract : Objectives: The usefulness of pharyngeal pH monitoring in patients with symptoms attributed to laryngopharyngeal reflux (LPR) has been questioned. One problem is the uncertainty whether the pharyngeal pH monitoring captures the aspects of LPR which are responsible for symptoms. We aimed to gain more insight into this problem by performing a comprehensive analysis of acidic pharyngeal reflux before and after the treatment with proton pump inhibitors (PPIs) in patients with suspected LPR. Methods: We used simultaneous pharyngeal and distal esophageal 24-hour pH/impedance monitoring to establish the gastroesophageal origin of pharyngeal reflux, and an unbiased approach to analysis by evaluating a whole range of pharyngeal reflux acidity (pH < 6, pH < 5.5, pH < 5.0, pH < 4.5 and pH < 4.0). Results: PPI treatment substantially (by ~50%) improved the symptoms attributed to LPR. In contrast, PPI did not reduce the number of pharyngeal reflux episodes or duration of pharyngeal acid exposure at any pH level. This was also true in a subgroup of patients considered to be good responders to PPI (symptoms improvement by ~75%). Furthermore, good responders did not have more acidic pharyngeal reflux than the patients who were less responsive to PPI. Conclusions: PPI treatment did not reduce acidic pharyngeal reflux despite substantially improving the symptoms attributed to LPR. This may be because pharyngeal pH monitoring does not quantitatively capture the aspects of LPR responsible for symptoms or because acid causes the symptoms also by mechanisms other than LPR. Our results argue against the utility of pharyngeal pH monitoring in patients with suspected LPR.